Análise da interação universidade-empresa-governo e o papel do Parque Científico e Tecnológico do Pampa para o desenvolvimento de startups - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Innovation environments are an element of extreme importance for the development of innovation and are characterized by providing favorable conditions for the development of innovative products and processes, among these innovation environments stand out the Scientific and Technological Parks. In view of the presented, this work aims to perform an analysis of the importance of the Federal University of Pampa and the Pampa Scientific and Technological Park for incubated startups, to detect the contributions of these agents, for the development of companies. For this, topics such as innovation were addressed, in Schumpeter's view; in the view of the Neoschumpeterians; science and technology; open innovation; triple helix and innovation ecosystem. The research was classified as applied, descriptive, qualitative, and case study. The questionnaire was chosen as a data collection instrument. Data were collected through the application of questionnaires to managers and companies related to Pampa Scientific and Technological Park, with this possible to perform content analysis, using Bardin’s model. It was verified the importance of Pampa Scientific and Technological Park and Government for the companies installed in this ecosystem of innovation and relationship of these actors with the Model of The Triple Helix.
Keywords: Inovação; Hélice Tríplice; Parque Científico e Tecnológico; Startups; Innovation; Triple Helix; Scientific and Technological Park; CNPQ::ENGENHARIAS